2023
DOI: 10.29228/jrp.336
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and ex vivo assessments of surfactant-free topical curcumin emulgel

Abstract: Curcumin has been used in many diseases due to its high therapeutical potential in recent years. Although curcumin is a frequently used natural polyphenolic compound products, its low solubility and poor permeability limits the dermal efficacy of curcumin. Emulgels are a new generation of semi-solid formulations that combine the advantages of both emulsions and gels. The biggest limitation of emulsions is surfactant related irritation problems caused by the use of high amount of surfactants. In this study, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…There are several reports available in the literature on the entrapment of curcumin in the classical emulsions, as well as in the Pickering emulsions [ 10 , 43 , 44 , 45 , 46 , 47 ]. These studies have mostly focused on the efficiency of the emulsions as a delivery vehicle for the release of curcumin into cells/tissues, which includes its dermal applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports available in the literature on the entrapment of curcumin in the classical emulsions, as well as in the Pickering emulsions [ 10 , 43 , 44 , 45 , 46 , 47 ]. These studies have mostly focused on the efficiency of the emulsions as a delivery vehicle for the release of curcumin into cells/tissues, which includes its dermal applications.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that a higher concentration of PGPR reduced the affinity between curcumin and the emulsion, thereby facilitating the release of curcumin through the Fickian mechanism. Furthermore, Ergin et al has reported the fabrication of a surfactant-free emulgel formulation of curcumin through the use of Carbopol 940 gels as the aqueous phase, and the use of an olive oil and curcumin methanol solution as the oily phase [ 44 ]. The obtained emulgels showed good mechanical, rheological, and spreadability properties, and also increased the transdermal permeation of curcumin.…”
Section: Discussionmentioning
confidence: 99%